(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
The differential transformation method (DTM) and Adomian decomposition method (ADM) are two numerical methods that can be used to solve various differential equations. In this work, we compare the accuracy, convergence, and computational complexity of these two methods by using them to solve second-order nonlinear equations using a new differential operator for the second-order equation. We also used both methods to solve second-order nonlinear differential equations.